MORTALITAS BENIH IKAN KOI (Cyprinus carpio) PADA KETINGGIAN DASAR MEDIA GABUS AMPAS TEBU DAN LAMA WAKTU PENGANGKUTAN YANG BERBEDA - Anggraini, Dwi; Taqwa, Ferdinand Hukama; Yulisman, Yulisman (Jurnal Perikanan dan Kelautan, 2014)
The aims of this research was determined the effect of the media cork bagasse base height and a long period to transportation on mortality of common carp fry and the average live common carp at the end of rearing. Fish used is common carp fry measuring 8.5 ± 0.5 cm and cork bagasse sized average of 5 ± 0.5 cm. The method used are completely randomized designed factorial pattern 3 x 3 where the first factor was height of basic media cork bagasse (T1 = 5 cm, T2 = 10 cm dan T3 = 15 cm) and the second factor was the length of time trans-portation (W1 = 2 hours, W2 = 4 hours dan W3 = 6 hours) and repeated 3 times. The results showed that the interaction of base height of media cork bagasse and the length of time trans-portation significant effect on mortality of common carp fry. The fastest of the recovered con-scious time showed in length of time the transportation 2 hours was 2.35 minutes, and the longest was 6.56 minutes on the transportation of 6 hours. This showed that the longer the transport time then recovered conscious time of common carp fry getting longer as well. The results of the best interaction was treatment T2W1, where had not fish mortality and avearge of common carp fry that live at the end of rearing for 7 days still maximum. Packing media temperature increased over increasing transport time, but for parameter chemical physics of water during rearing was still within the normal range rearing common carp fry.